The Son - Nesbo, Jo, 1960-; Barslund, Charlotte (London : Harvill Secker, 2014)
Sonny is a model prisoner. He listens to the confessions of other inmates at Oslo jail, and absolves them of their sins. Some people even whisper that Sonny is serving time for someone else: that he doesn't just listen, he confesses to their crimes. Inspector Simon Kefas is a dedicated police officer and has worked for the Oslo police force for years. He's just been assigned a new murder investigation and a new partner, all on the same day. Both of them knew Sonny's father. To Sonny he was the man he idolised, to Simon he was his best friend. Both were left devastated when his corruption was revealed. But neither of them knew the truth.
Translated from the Norwegian by Charlotte Barslund.
Keywords: Oslo (Norway) -- Fiction; Suspense fiction